PENDAMPINGAN PENYUSUNAN DAN PERENCANAAN ANGGARAN SEKOLAH GUNA MENINGKATKAN SUMBER DAYA MANUSIA PENGELOLA KEUANGAN DI SMK ARDJUNA 2 ARJOSARI MALANG - Wany, Eva; Prayitno , Budi; Yustie, Renta (Journal of Social Comunity Services, 2024)
Financial management in an organization is an important aspect to build a sound and credible organizational governance. The SMK Ardjuna 2 Arjosari Malang, including schools and other educational institutions, has grown quite rapidly both in number and in the value of its assets so that it requires good management in order to create a good and dignified organization.